Whole Exome Sequencing Reveals a Novel APOE Mutation in a Patient With Sporadic Early-Onset Alzheimer's Disease - Bagaria, Jaya; Moon, Yeonsil; Bagyinszky, Eva; Shim, Kyu Hwan; An, Seong Soo A.; Kim, SangYun; Han, Seol Heui (Frontiers in Neurology, 2022)
Apolipoprotein (APOE) is implicated and verified as the main risk factor for early onset Alzheimer’s disease (AD). APOE is a protein that binds to lipids and is involved in cholesterol stability. Our paper reports a case of a sporadic AD patient of 54-year-old Korean man, where a novel APOE Leu159Pro mutation was revealed upon Whole Exome Sequence analysis. The proband’s CSF showed downregulated levels of Aβ42, with unchanged Tau levels. The mutation is in the Low-Density Lipoprotein Receptor (LDLR) region of APOE gene, which mediates the clearance of APOE lipoproteins. LDLR works as a high affinity point for APOE. Studies suggest that APOE-LDLR interplay could have varying effects. The LDLR receptor pathway has been previously suggested as a therapeutic target to treat tauopathy. However, the APOE-LDLR interaction has also shown significant correlation with memory retention. Leu159Pro could be an interesting mutation that could be responsible for a less damaging pattern of AD by suppressing tau-association neurodegeneration, while affecting the patient’s memory retention and cognitive performance.